Nutritionally Enhanced Edible Oil Processing 2004
DOI: 10.1201/9781439822272.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion-Based Oilseed Processing Methods

Abstract: Oilseeds occupy an important place in global agriculture by providing vegetable oils and high-protein meals for food, feed, and industrial uses. The leading oilseed crops by volume of world production are soybean, cottonseed, peanut, sunflower, rapeseed (canola), copra (coconut), and palm. The combined world production of these major oilseed crops in [2001][2002] The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Nelson et al ( 17 ) reported that up to 59% of the oil in whole soybeans could be removed by the extrusion expelling process, leaving a soy cake with 6–9% oil. Similarly, Wijeratne et al ( 49 ) reported that the amount of oil in low-fat soy cake after extruding expelling processing ranges between 6 to 9%. Despite its cost, it is possible to capture this oil washed away using a multiphase decanter centrifuge.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nelson et al ( 17 ) reported that up to 59% of the oil in whole soybeans could be removed by the extrusion expelling process, leaving a soy cake with 6–9% oil. Similarly, Wijeratne et al ( 49 ) reported that the amount of oil in low-fat soy cake after extruding expelling processing ranges between 6 to 9%. Despite its cost, it is possible to capture this oil washed away using a multiphase decanter centrifuge.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that dry extrusion applied during an extrusion-expelling combined process disrupts the integrity of the cellular structure of soybean cotyledon, which facilitates oil release from subcellar structures. This extrusion process turns the soybean material into a more homogenous matrix at a semifluid state and the oil becomes readily available to press out at the screw-pressing step ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Haider, personal communication), while a literature source indicated operating air temperatures of 150-160 • C in that time period (Wilmot-Wijeratne et al, 2004).…”
Section: 12mentioning
confidence: 98%
“…As a result, these researchers recommended that to minimize the risk of ASFV transmission as much as possible, crops from ASFVaffected zones should not be used for pig feed. Furthermore, Bok- 2015, 1005.90.2025, 1005.90.4040, 1005.90.4060. device equipped with a rotating screw in a closed barrel that transports feed material through varying conditions of heat, shear and pressure (Wijeratne et al, 2004). The screw speed of the extruder is typically 600 rpm with varying temperature ranging from 130 to 160 • C (Wijeratne et al, 2004).…”
Section: Potential Sources Of Soybean Contamination In Asfv-positive Countries Of Originmentioning
confidence: 99%
“…Furthermore, Bok- 2015, 1005.90.2025, 1005.90.4040, 1005.90.4060. device equipped with a rotating screw in a closed barrel that transports feed material through varying conditions of heat, shear and pressure (Wijeratne et al, 2004). The screw speed of the extruder is typically 600 rpm with varying temperature ranging from 130 to 160 • C (Wijeratne et al, 2004). After the extruder, the soybean cake will undergo drying/cooling depending on the type of extruder used to process the soybeans.…”
Section: Potential Sources Of Soybean Contamination In Asfv-positive Countries Of Originmentioning
confidence: 99%